Cedaw in the Eyes of the United States - AL SHRAIDEH, Saleh (Journal of Legal Studies, 2017)
Despite the large number of reservations registered by Member countries, making it one of the, if not the, most heavily reserved human rights treaties; the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) has managed to achieve a very high rate of states‟ membership [1]. Currently, 187 countries out of the 193 United Nations Members are parties to CEDAW [2]. What is strange to digest, however, is the fact that the United States is one of the seven countries that are yet to ratify the Convention [3]. This article provides an insight into the position of the United States from the ratification of CEDAW. It examines the merits of arguments made for and against the ratification and their rationale to provide a better understanding that explains what is considered by many as a buzzling stand of the United States from the Convention.